International Remittances and Private Schooling: Evidence from Kerala, India - C. Valatheeswaran and M. Imran Khan (International Migration, 2018)
This study investigates the impact of international remittances on private school enrolment in Kerala. Using data from the 2010 Kerala Migration Survey and employing an instrumental variable (IV-Probit) approach to address the endogeneity of migration, we found that remittances have a positive and significant effect on private school enrolment. After disaggregating the sample into different heterogeneous groups, we found that remittances have greater effect on boys, children residing in rural areas, and those belonging to socially advantageous groups and from higher wealth quintile. Children from lower wealth quintile and belonging to socially disadvantageous groups are least affected by migration and remittances.